Effect of Carbon Black Content on the Properties of Polyamide Coating on CuCr Alloy Surface for Sensor - ZHANG Yue - xia, ZHAO Shang - li, LIU Zhi - yong (Cailiao Baohu)
In order to improve the corrosion resistance of the micro - arc oxide layer on the by experimental tests CuCr alloy surface for sensor, polyamide coatings were prepared by setting different amount of carbon black. The ratio of epoxy resin to acetone was set at 5∶3(mass ratio, the same below). The influence of each component on corrosion resistance and electrical conductivity of the coating was analyzed by experimental tests. Results showed that when the content of carbon black particles reached 10%, the adjacent carbon black particles formed a more compact arrangement in the coating, presenting a more compact filling effect on the voids. When the amount of carbon black particles was increased, more obvious surface defects were formed. And both the size and the amount of carbon black particles in the coating were obviously increased. With the increase of the amount of carbon black, the corrosion resistance of the coating increased first and then decreased. At the carbon black content of 10%, the corrosion resistance of the coating was better. The use of polyamide coating could achieve the effect of microporous sealing, so that the number of reactive points was reduced, effectively improving the corrosion resistance of the coating. When the content of carbon black particles reached 10%, the resistance of the coating decreased, and the minimum resistance value was obtained to achieve better conductivity. After increasing the content of carbon black particles, the conductive network could be connected to obtain the minimum coating resistance.